Extrapulmonary Tuberculosis: Epidemiology, Risk Factors and Distribution Trends - Berdieva, Dilrabo Azimovna; Dinora, Abduvohidova (American Journal of Biomedicine and Pharmacy, 2025)
The article analyzes the epidemiological situation of extrapulmonary tuberculosis (EPTB) in the Republic of Uzbekistan. An increase in extrapulmonary organ involvement has been observed in recent years. The study examines risk factors, socio‑economic and biological causes, and patterns in disease spread.